Analisis Efisiensi Trafo 20 kV/150 kV GT pada PT Indonesia Power PLTU Banten 2 Labuan Unit 1 dan 2 dalam Pengaruh Beban - Gera Nugraha; Irwanto, Irwanto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
A transformer is an electrical equipment that converts alternating current voltage from low voltage to high voltage or vice versa. At PT Indonesia Power UJP PLTU Banten 2 Labuan, power transformers have an important role in the production of electrical energy and its continuity. The loading pattern of PT Indonesia Power UJP PLTU Banten 2 Labuan varies, mainly due to usage. Residential sector consumers are the intended users of electrical energy. Transformer variable loads experience losses as a result. The loss of iron core can result in excessive heat and vibration in the transformer, thus lowering its efficiency level. This study aims to determine the effect of fluctuating loads on the efficiency value of transformers at PT Indonesia Power UJP PLTU Banten 2 Labuan. By analyzing the ratio of incoming power to outgoing power and the amount of power lost, we can determine how much impact load changes have. Based on the analysis results, the most efficient load is at 08.00 and 12.00 with an efficiency value of 98.16% for unit 1, while for unit 2 it is at 07.00 and 09.00 with a value of 99.59%. The findings of the analysis allow us to draw the conclusion that the efficiency value is always changing as it decreases when the load fluctuates.